Ultrasound criteria of extra-nodal extension in papillary thyroid cancer metastases and its clinical signifcance - V. S. Parshin; P. I. Garbuzov; V. V. Polkin; E. I. Kupriyanova; P. A. Isaev; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2024)
The purpose of the research was to identify ultrasound criteria of extranodal extension (ENE) in metastases of papillary thyroid cancer and to evaluate the clinical significance of ENE.Material and Methods. Ultrasound signs of ENE in 283 cervical lymph node metastases from papillary thyroid cancer were analyzed. Extranodal extension in 137 metastases was diagnosed by ultrasound and verified by histological examination. Micrometastases invisible on ultrasound were detected in 144 patients; metastases located inside the organ were detected in 147 patients; metastases located outside the organ were revealed in 136 patients; the size of 98 metastases was less than 1 cm; the size of 185 metastases was more than 1 cm; the age of 51 patients was under 55 years; 132 patients were older than 55 years. Diagnostic significance of ENE and its clinical significance were estimated according to χ2 Pirson criteria.Results: Two ultrasound criteria: shape change and blurred margins of metastases indicated the presence of ENE. The small number of ultrasound false-negative findings indicated the need for further research. The number of micrometastases not detected by ultrasound was 2-fold higher in patients who had metastases with ENE than in patients who had metastases without ENE. The number of patients with ENE in metastases inside the organ (T1a, T1b, T2 and T3b) was 2.7 times lower compared to patients with metastases developed outside the organ (T3a, T4a, T4b); ENE was observed in metastases of different size and did not depend on age groups.Conclusion. The ultrasound method allows intravital detection of ENE in metastases of papillary thyroid cancer. The extension is accompanied by a significantly high number of micrometastases in the neck tissue. It is detected more often in metastases located outside the organ, regardless of the size and age of the patients. The extra-nodal extension should be considered as a criterion for an unfavorable prognosis.